2021
DOI: 10.1007/s10344-021-01495-1
|View full text |Cite
|
Sign up to set email alerts
|

Modelling stakeholder satisfaction for conflict resolution in wildlife management: a case of wolf population in Sweden

Abstract: The Swedish wolf population has rebounded from near extinction in the 1960s to around 365 individuals in 2020, after the implementation of the Hunting Act (jaktlagen) in 1966. This recent increase in the wolf population has evoked a serious divide between “pro-wolf” and “anti-wolf” Swedish citizens. Despite the continuous efforts by the Swedish government to reconcile this antagonism, the conflicts are persistent with a sign of impasse. In this paper, we present a modelling tool, which can bring transparent an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 77 publications
(127 reference statements)
1
2
0
Order By: Relevance
“…We found that satisfaction with grizzly bear management followed the Goldilocks principle where satisfaction peaks when people perceive that wildlife population levels are neither too high nor too low (Figures 3–5a). Our findings are consistent with at least one other study relating satisfaction with preferred wolf population sizes for different interest groups in Sweden (Lin et al, 2021). Satisfaction measures, when applied to conservation of large carnivores such as grizzlies, may provide one important social indication of coexistence.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…We found that satisfaction with grizzly bear management followed the Goldilocks principle where satisfaction peaks when people perceive that wildlife population levels are neither too high nor too low (Figures 3–5a). Our findings are consistent with at least one other study relating satisfaction with preferred wolf population sizes for different interest groups in Sweden (Lin et al, 2021). Satisfaction measures, when applied to conservation of large carnivores such as grizzlies, may provide one important social indication of coexistence.…”
Section: Discussionsupporting
confidence: 93%
“…For example, large carnivores can drive tourism and are often the face of conservation campaigns because many people highly value these animals (Chambers & Whitehead, 2003; Naidoo et al, 2011; Richardson & Loomis, 2009; Thomas‐Walters & Raihani, 2017). On the other hand, opposition to large carnivore recovery can stem from real or perceived risks to human values and safety (Hughes & Nielsen, 2019; Lin et al, 2021; Riley & Decker, 2000; Stone et al, 2017). Despite this common “for or against” framing, evidence suggests large carnivore conservation is far more complex, where people can see the value of large carnivores and the risks they impose (Zajac et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation